Mitochondrial dysfunction precedes hippocampal IL-1β transcription and cognitive impairments after low-dose lipopolysaccharide injection in aged mice - Yulim Lee; Xianshu Ju; Jianchen Cui; Tao Zhang; Boohwi Hong; Yoon Hee Kim; Youngkwon Ko; Jiho Park; Chul Hee Choi; Jun Young Heo; Woosuk Chung (Heliyon, 2024)
Acute cognitive impairments termed delirium often occur after inflammatory insults in elderly patients. While previous preclinical studies suggest mitochondria as a target for reducing neuroinflammation and cognitive impairments after LPS injection, fewer studies have evaluated the effects of a low-grade systemic inflammation in the aged brain. Thus, to identify the significance of mitochondrial dysfunction after a clinically relevant systemic inflammatory stimulus, we injected old-aged mice (18–20 months) with low-dose lipopolysaccharide (LPS, 0.04 mg/kg). LPS injection reduced mitochondrial respiration in the hippocampus 24 h after injection (respiratory control ratio [RCR], state3u/state4o; control = 2.82 ± 0.19, LPS = 2.57 ± 0.08). However, gene expression of the pro-inflammatory cytokine IL-1β was increased (RT-PCR, control = 1.00 ± 0.30; LPS = 2.01 ± 0.67) at a more delayed time point, 48 h after LPS injection. Such changes were associated with cognitive impairments in the Barnes maze and fear chamber tests. Notably, young mice were unaffected by low-dose LPS, suggesting that mitochondrial dysfunction precedes neuroinflammation and cognitive decline in elderly patients following a low-grade systemic insult. Our findings highlight mitochondria as a potential therapeutic target for reducing delirium in elderly patients.